Does traumatic brain injury lead to criminality? A whole-population retrospective cohort study using linked data - Schofield, P.; Malacova, E.; Preen, D.; D'Este, C.; Tate, R.; Reekie, J.; Wand, H.; Butler, Tony (2015)
© 2015 Schofield et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background: Traumatic brain injury (TBI) may be a risk factor for criminal behaviour however multiple factors potentially confound the association. Methods: Record linkage and Cox proportional hazards regression analyses were used to examine the association between hospital-recorded TBI (n = 7,694) and subsequent first criminal conviction in a retrospective cohort matched 1:3 with 22,905 unaffected community controls and full-sibling controls (n = 2,397). Aboriginality, substance abuse, social disadvantage, and mental illness were included in analyses as potential confounders Results: In multivariable models, relative to general population controls, TBI was associated with any conviction (males: Hazard Ratio (HR) = 1.58 (95% CI 1.46 to 1.72); females: HR = 1.52 (95% CI 1.28 to 1.81)); and similar Hazard Ratios were obtained for the sibling analyses in males (HR = 1.68 (95% CI 1.31-2.18)) and females (HR 1.27 (95% CI 0.71-2.29)). TBI was also associated with violent convictions relative to the general population, (males: HR = 1.65 (95% CI 1.42 to 1.92); females HR = 1.73 (95% CI 1.21 to 2.47)), and in analyses with sibling controls in men (HR = 1.89 (95% CI 1.20-3.00)), but not in women (HR 0.73, 95% CI 0.29-1.81)). Conclusion: The results support a modest causal link between TBI and criminality after comprehensive adjustment for confounding. Reducing the rate of TBI, a major public health imperative, might have benefits in terms of crime reduction.